Bhopal Revisited. Issue 4 (December 2014) - Murphy, John F.; Hendershot, Dennis; Berger, Scott; Summers, Angela E.; Willey, Ronald J.
<x xml:space="preserve">Abstract</x> On December 3, 1984, a pesticide plant in Bhopal, India released approximately 40 metric tons of methyl isocyanate into the atmosphere. The impact of this incident was an estimated 2, 000 fatalities, 100, 000 injuries, and significant damage to livestock and crops [1]. Thirty years have passed since this event occurred but the impact of this event on the chemical processing industries and the people who work in it has not been forgotten. In remembrance of this event, I asked several well‐known process safety experts that had the opportunity to visit the Bhopal site in 2004 each to write a short article that speaks to the personal impact of Bhopal on their careers in the chemical processing industries. Below are their personal and thoughtful responses to my request. © 2014 American Institute of Chemical Engineers Process Saf Prog 33: 310–313, 2014